Elucidation of Switching Mechanisms in Memristive Junctions Integrating a Iron(II)‐Ter Pyridine Diazoted Complex - Camille Jubert Tomasso; Thomas Petenzi; Anna Tidu; Rassen Boukraa; Sofia Russi; Giorgio Mattana; Christelle Gautier; Tony Breton; Ivan T. Lucas; Hubert Perrot; Laure Fillaud (Advanced Electronic Materials)
Abstract An original way of elaborating vertical metal/molecules/metal memristive junctions through diazonium electrografting of the organic layer and inkjet‐printed top electrodes is reported here. The molecule of interest is a FeII coordination complex with ter‐pyridine ligands, having a diazonium anchoring group. The resulting junction exhibits a memristive behavior characterized by a high ON/OFF ratio and plasticity property. Through the application of advanced techniques such as UV–vis and Raman time‐resolved spectroelectrochemistry, the study demonstrates the significant role of switchable azo bonds derived from diazo electrografting in memristive behavior.